Loss of salt tolerance during tomato domestication conferred by variation in a Na+/K+ transporter. (5th March 2020) - Wang, Zhen; Hong, Yechun; Zhu, Guangtao; Li, Yumei; Niu, Qingfeng; Yao, Juanjuan; Hua, Kai; Bai, Jinjuan; Zhu, Yingfang; Shi, Huazhong; Huang, Sanwen; Zhu, Jian‐Kang
Abstract: Domestication has resulted in reduced salt tolerance in tomato. To identify the genetic components causing this deficiency, we performed a genome‐wide association study (GWAS) for root Na + /K + ratio in a population consisting of 369 tomato accessions with large natural variations. The most significant variations associated with root Na + /K + ratio were identified within the gene SlHAK20 encoding a member of the clade IV HAK/KUP/KT transporters. We further found that SlHAK20 transports Na + and K + and regulates Na + and K + homeostasis under salt stress conditions. A variation in the coding sequence of SlHAK20 was found to be the causative variant associated with Na + /K + ratio and confer salt tolerance in tomato. Knockout mutations in tomato SlHAK20 and the rice homologous genes resulted in hypersensitivity to salt stress. Together, our study uncovered a previously unknown molecular mechanism of salt tolerance responsible for the deficiency in salt tolerance in cultivated tomato varieties. Our findings provide critical information for molecular breeding to improve salt tolerance in tomato and other crops. Synopsis: Selection of large fruits in domesticated tomato is linked to a reduction in salt tolerance. This study links domestication‐associated variation in the Na + /K + transporter‐coding gene SlHAK20 to reduced salt tolerance in cultivated plants. Root Na + /K + ratios show a strong positive correlation with fruit weight during tomato domestication. A variation in SlHAK20 is associated with Na + /K + ratio modulation in tomato roots under salt stress conditions. The SlHAK20 Hap1 haplotype is more effective than SlHAK20 Hap2 in conferring Na + homeostasis and salt tolerance. The role of SlHAK20 in regulation of salt tolerance is conserved in rice. Abstract : A genome‐wide association study links reduced sodium ion uptake by SlHAK20 transporter to diminished salt tolerance and increased fruit weight in cultivated tomato.